A theory of contingent business process management. Issue 6 (4th December 2018) - Zelt, Sarah; Recker, Jan; Schmiedel, Theresa; vom Brocke, Jan
Abstract : Purpose: Many researchers and practitioners suggest a contingent instead of a "one size fits all" approach in business process management (BPM). The purpose of this paper is to offer a contingency theory of BPM, which proposes contingency factors relevant to the successful management of business processes and that explains how and why these contingencies impact the relationships between process management and performance. Design/methodology/approach: The authors develop the theory by drawing on organizational information processing theory (OIPT) and applying an information processing (IP) perspective to the process level. Findings: The premise of the model is that the process management mechanisms such as documentation, standardization or monitoring must compensate for the uncertainty and equivocality of the nature of the process that has to be managed. In turn, managing through successful adaptation is a prerequisite for process performance. Research limitations/implications: The theory provides a set of testable propositions that specify the relationship between process management mechanisms and process performance. The authors also discuss implications of the new theory for further theorizing and outline empirical research strategies that can be followed to enact, evaluate and extend the theory. Practical implications: The theory developed in this paper allows an alternative way to describe organizational processes and supports the derivation of context-sensitive management approaches for process documentation, standardization, monitoring, execution and coordination. Originality/value: The theoretical model is novel in that it provides a contextualized view on BPM that acknowledges different types of processes and suggests different mechanisms for managing these. The authors hope the paper serves as inspiration both for further theory development as well as to empirical studies that test, refute, support or otherwise augment the arguments.